(untitled) (Annals of Medical Research, 2021)
Aim: To compare open and closed systems in the preparation of Platelet Rich Plasma (PRP) in terms of feasibility, cost, and safety. Materials and Methods: In this prospective study 10 patients who were undergoing controlled ovarian hyperstimulation and intrauterine insemination, were included. Open system PRP prepeared from these patients collected blood which have the highest number of platelets. Open system PRP’s platelet concentration and cost were compared with closed system kit. Results: It was found that 778g (2000rpm) was the best centrifugal force, and 5 minutes was the optimum duration for having the highest level of platelets. The mean platelet concentrations in the open system (425 ± 91.2 × 103/ml) were statistically significantly higher than the closed system (298 ± 88.32 × 103/ml) (p = 0.021). No growth was observed in the culture inoculated with PRPs obtained using open system. In the cost analysis, the open system was significantly more economic than the closed system. Conclusions: Higher platelet concentrations can be achieved using a low-cost sterile open system centrifugation method than the closed system kit in the laboratory setting effectively.